The prevalence of human papillomavirus genotypes (HPV-6, HPV-11, HPV-16, and HPV-18) in the unilateral and bilateral nasal polyps - Amani M Abd Elwahab; Randa A Abdullah; Gehan S Shalaby; Soad Yehia; Hanaa Aboeliazed (Al-Azhar Assiut Medical Journal, 2017)
Aim The aim of this study was to investigate the prevalence of different genotypes (HP-6, HP-11, HP-16, and HP-18) of human papillomavirus (HPV) in nasal polyps (NPs). Materials and methods This is a prospective, comparative, controlled study. A total of 24 patients with NPs along with 10 patients with deviated nasal septum without NPs (as controls) were enrolled. Biopsy specimens from the patients’ NPs and from nasal mucosa of controls were collected for the detection of the four HP genotypes using PCR-based DNA amplification using the genotype-specific primers (6/E5, 11/L1, 16/L1, and 18/L1). Results An overall 91% (22/24) of patients with NPs were found to be positive for HPV infection, whereas all participants of the control group were negative (P<0.05). Among the HP-positive cases, 19/22 (86.3%) were infected with a single genotype, whereas 3/22 (13.6%) demonstrated a coinfection of HP-11 and HP-18 genotypes. The HP-18 was found to be the most prevalent genotype [8/22 (36.36%)]. However, the occurrence of the HP-6 genotype was higher [6/22 (27.27%)] than that of the HP-11 [5/22 (22.7%)]; HP-16 was not detected in any of the unilateral or bilateral NP specimens. Conclusion Our findings suggest that the HPV infection is associated with the formation of NPs and further investigation is imperative to define a correlation between the two.